Blogging for Dummies - Hill, Brad (Wiley Publishing, 2011)
If you want to give yourself a Web presence without spending a lot of time or money, a blog is your answer and this is your guide. Blogs (Web logs) are short, diary-like entries on a Web site that has a chronological, journal format. Fun or informative, but not formal, blogs are easy to set up, maintain, and update. You can share your personal, stream-of-consciousness musings or your expertise on any subject ranging from your family vacation to world peace. This guide helps beginners (even technophobes) get started fast, with the essential info on: